Utilizing the Canva Application in Teaching Fiqh - Burhanuddin, Burhanuddin; Febriani, Afifah; Hoktaviandri, Hoktaviandri; Simbolon, Muhammad Kosim; Vanessa, Anadya Diva (Al-Hashif: Jurnal Pendidikan dan Pendidikan Islam, 2025)
This study is motivated by the low learning interest of students in the Fiqh subject at Madrasah Aliyah (MA), which necessitates innovative learning media that are more engaging and aligned with technological developments. One of the media utilized is the Canva application, which can present material in a visual, creative, and easily understandable manner. The purpose of this study is to describe the steps of utilizing Canva-based media by Fiqh teachers to increase students’ learning interest and to identify its advantages and disadvantages in the learning process. This research employs a qualitative approach with a descriptive method, where data are collected through observation, interviews, and documentation, and then analyzed using data reduction, data presentation, and conclusion drawing techniques. The results of the study indicate that Fiqh teachers implement Canva utilization through stages of planning, media creation, learning implementation, student participation, and evaluation. The use of Canva has proven advantages, including attractive visual displays, ease of use, time efficiency, and the ability to enhance students’ motivation and creativity. However, there are also challenges, such as internet connectivity limitations, restrictions on free features, differences in students’ digital skills, and unequal access to devices. Overall, the utilization of Canva contributes positively to increasing students’ learning interest in the Fiqh subject.